The Effect of Corporate Governance, Company Size and Leverage on Profit Management and Financial Performance in the Registered Mining Sector on BEI 2012-2016 (International Journal of Business and Information Technology, 2022)
The purpose of this study was to determine and analyze the effect of institutional ownership on earnings management. To find out and analyze the effect of managerial ownership on earnings management. To find out and analyze the effect of the size of the board of commissioners on earnings management. To find out and analyze the effect of the proportion of independent commissioners on earnings management. To find out and analyze the effect of the size of the audit committee on earnings management. To find out and analyze the effect of firm size on earnings management. To find out and analyze the effect of leverage on earnings management. To determine and analyze the effect of institutional ownership on financial performance. To find out and analyze the effect of managerial ownership on financial performance. To find out and analyze the effect of the size of the board of commissioners on financial performance. To find out and analyze the effect of the proportion of independent commissioners on financial performance. To determine and analyze the effect of the size of the audit committee on financial performance. To find out and analyze the effect of firm size on financial performance. To find out and analyze the effect of leverage on financial performance. To determine the effect and analyze the effect of earnings management on financial performance. The result of this research is that institutional ownership has no effect on earnings management. This explains that the occurrence of earnings management has no influence on the institutions that have shares in the company concerned. Managerial ownership has no effect on earnings management. This explains that the occurrence of earnings management has no influence from the directors or managers who have shares in the company concerned. The size of the board of commissioners has no effect on earnings management. This explains that the occurrence of earnings management has no effect on the number of commissioners in the company concerned. The proportion of independent commissioners has no effect on earnings management. This explains that the occurrence of earnings management has no effect on the proportion of independent commissioners owned by the company concerned. The size of the audit committee has no effect on earnings management. This explains that the occurrence of earnings management has no effect on the number of audit committees in the company concerned. Firm size has no effect on earnings management. This explains that the occurrence of earnings management has no effect on the size of the company in the company concerned. Leverage has no effect on earnings management. This explains that the occurrence of earnings management has no effect on the debt owned by the company concerned. Institutional ownership has no effect on financial performance. This explains that institutional ownership does not have any effect on the financial performance of a company. Managerial ownership has an influence on financial performance. This explains that share ownership owned by directors and managers has an influence on the company's financial performance. The size of the board of commissioners has no effect on financial performance. This explains that the size or number of commissioners does not affect the financial performance of a company. The proportion of independent commissioners has no effect on financial performance. This explains that the number of independent commissioners does not affect the financial performance of a company. The size of the audit committee has no effect on financial performance. This explains that the number of audit committees has no effect on the financial performance of a company. Company size has no effect on financial performance. This explains that the size of a company does not affect the good or bad financial performance of a company. Leverage has an influence on financial performance. This explains that the good or bad financial performance of a company, one of which is influenced by leverage. Earnings management has no effect on financial performance. Whether or not earnings management is applied to a company will not have an effect on financial performance.